Effect of mercerization on the chemical characteristics of plant-based natural fibers. (2022) - Prem Kumar, N.; Chellapandian, M.; Arunachelam, N.; Vincent, P.
Abstract: In this study, the microstructure and chemical characterization of untreated and alkaline treated plant-basednatural fibers such as pineapple, kenaf, flax, hemp were performed. The objective of the present work is to understand the effectiveness of mercerization on the characteristics of plant-based natural fibers. First, the raw untreated fibers was subjected to treatment in 5% NaOH solution for the removal of surface impurities and thereby enhancing the hydrophobic nature of fibers. After NaOH treatment, the fibers were washed 3–4 times with distilled to remove the sodium hydroxide settlements during mercerization. The microstructure analysis of the untreated and treated fibers was performed using the Field Emission Scanning Electron Microscope (FESEM). Moreover, the elemental composition was studied using the Energy Dispersive X-ray Spectroscopy (EDS).Results from the FESEM analyses revealed that the alkaline treatment of raw fibers using NaOH helped in the removal of surface impurities, lignin, and hemicellulose. Moreover, the elemental composition obtained from EDS analysis showed an increased amount of carbon content in untreated fibers.